Reciprocal signaling between adipose tissue depots and the central nervous system - Puente-Ruiz, Stephanie C.; Jais, Alexander (Frontiers in Cell and Developmental Biology, 2022)
In humans, various dietary and social factors led to the development of increased brain sizes alongside large adipose tissue stores. Complex reciprocal signaling mechanisms allow for a fine-tuned interaction between the two organs to regulate energy homeostasis of the organism. As an endocrine organ, adipose tissue secretes various hormones, cytokines, and metabolites that signal energy availability to the central nervous system (CNS). Vice versa, the CNS is a critical regulator of adipose tissue function through neural networks that integrate information from the periphery and regulate sympathetic nerve outflow. This review discusses the various reciprocal signaling mechanisms in the CNS and adipose tissue to maintain organismal energy homeostasis. We are focusing on the integration of afferent signals from the periphery in neuronal populations of the mediobasal hypothalamus as well as the efferent signals from the CNS to adipose tissue and its implications for adipose tissue function. Furthermore, we are discussing central mechanisms that fine-tune the immune system in adipose tissue depots and contribute to organ homeostasis. Elucidating this complex signaling network that integrates peripheral signals to generate physiological outputs to maintain the optimal energy balance of the organism is crucial for understanding the pathophysiology of obesity and metabolic diseases such as type 2 diabetes.